ILLOCUTIONARY ACTS AND POLITENESS STRATEGIES IN EFL CLASSROOM INTERACTION AND THE STUDENTS' PERCEPTIONS - Mida Alifia Soviana; Nurul Mukminatien (Universitas Negeri Malang, 2020)
Abstract: This study explores illocutionary acts and politeness strategies employed by the academic staff and also the students' perceptions on the academic staff's language and politeness strategies in EFL classroom interaction. Twelve different classes of six English academic staff in one term lasting 100 minutes each were observed and recorded and then transcribed. The results showed that four out of five types of illocutionary acts were employed; directive, representative, commisive, and expressive. Concerning the use of politeness strategies in the academic staff's illocutionary acts, bald on-record, positive, negative and off-record politeness strategies were all employed. This study also indicates that most of the university students expressed agreement to the use of polite language in the classroom interaction.  Key words: illocutionary acts, face threatening acts, politeness strategies, perception Abstrak:Penelitian ini membahas tentang tindak ilokusi dan strategi kesopanan yang digunakan oleh para dosen dan persepsi dari mahasiswa mereka terkait penggunaan bahasa dan strategi kesopanan oleh dosen di interaksi kelas Bahasa Inggris sebagai Bahasa Asing. Dua belas kelas yang berbeda dari enam dosen Bahasa Inggris dengan waktu pertemuan masing-masing 100 menit telah diobservasi, direkam, dan ditranskrip. Hasil dari penelitian ini menunjukkan bahwa para dosen menggunakan empat dari lima macam tipe tindak ilokusi, yaitu: direktif, representatif, komisif, dan ekspresif. Sehubungan dengan strategi kesopanan yang ditemukan di tindak ilokusi para dosen, disimpulkan bahwa para dosen menggunakan tipe kesopanan bald on-record, kesopanan positif, kesopanan negatif, dan kesopanan off-record. Penelitian ini juga menunjukkan bahwa sebagian besar mahasiswa setuju atas penggunaan bahasa yang sopan di dalam interaksi kelas. Kata kunci: tindak tutur ilokusi, tindak tutur ancaman, strategi kesopanan, persepsi